The Responsibility of Science - Mieg, Harald A. (Studies in History and Philosophy of Science, 2022)
This open access book provides an overview of issues of scientific responsibility. The volume comprises three types of contributions: first, analyses of the responsibility of science; second, analyses of the structural conditions for science and its responsibility; and third, normative versions of scientific responsibility. The questions and problems dealt with include science as a profession, ambivalence of research and dual-use, innovation vs. precaution, notions of responsibility, the role of science within society and its relation to human rights, as well as scientific and public discourses. The book addresses scholars in the fields of Science Studies and Research Policy. This is an open access book.